Bahasa Inggris - Rifqah Najwa Azizah; Yusuf Rahman (Jurnal Kawakib, 2025)
This study examines the issue of religious authorities intervening through fatwas, which often have implications for restricting individual freedom. This problem arises because fatwas, which are intended to be moral guidelines and non-binding laws, are frequently used in practice as tools and instruments of social control, thereby limiting individual autonomy. This research aims to explore the concept of freedom in the context of religious authority by examining the idea of freedom in Islam. Methodically, this study employs a qualitative research method in library research. Meanwhile, data analysis was carried out in a descriptive-analytical mannerThe results of this study emphasize the importance of freedom as a human right, and there should be no intervention from other parties, including fatwas issued by religious authorities. The intervention of the authorities is limited to protection from crime and hypocrisy, including the issuance of fatwas; it is necessary to consider the right to liberty and justice of every individual. The conclusion of this study reveals that opening the reason of freedom means placing human beings as an end, not as an object or tool of other parties' interests. This study contributes to the fields of theology and philosophy, particularly in liberal Islamic thought, which emphasizes individual freedom as ande critical study of freedom in the context of religious authority.